2021
DOI: 10.1007/s00702-021-02312-4
|View full text |Cite
|
Sign up to set email alerts
|

Consensus guidelines for botulinum toxin therapy: general algorithms and dosing tables for dystonia and spasticity

Abstract: Botulinum toxin (BT) therapy is a complex and highly individualised therapy defined by treatment algorithms and injection schemes describing its target muscles and their dosing. Various consensus guidelines have tried to standardise and to improve BT therapy. We wanted to update and improve consensus guidelines by: (1) Acknowledging recent advances of treatment algorithms. (2) Basing dosing tables on statistical analyses of real-life treatment data of 1831 BT injections in 36 different target muscles in 420 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 21 publications
1
37
0
4
Order By: Relevance
“…We further analyzed the doses for each muscle and compared them with a recently published consensus guideline [21]. The average dose for SCM, LS, SPC and scalenus in the present study was similar to the guideline.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…We further analyzed the doses for each muscle and compared them with a recently published consensus guideline [21]. The average dose for SCM, LS, SPC and scalenus in the present study was similar to the guideline.…”
Section: Discussionmentioning
confidence: 64%
“…Possible reason could be that the strategy we used in most patients was to distribute the dose according to the image of SPECT/CT rather than increase the total dose. However, in future studies, increase of total dose could also be considered if we observed both activation of superficial and deep muscle, because the purpose of BTX-A injection is to "Hit the right muscle with the right dose" [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, follow-up duration in both long-term studies was only 10 years and no specific BoTX dosage in musicians in the latter study was reported. Furthermore, our median dosage was higher than the recommended dosage of 19.9 MU BoTX for the finger flexor muscles in WC in the recently published consensus guideline for BoTX therapy [ 32 ].…”
Section: Discussionmentioning
confidence: 78%
“…La toxina se reconstituyó con BBS y el volumen en total no excedió los 5 ml, de hecho, se administraron 2,5 ml en cada músculo. También en este caso se siguieron las recomendaciones generalizadas de emplear el menor volumen posible, pero adecuada al músculo a tratar, para evitar una difusión indeseable a estructuras vecinas (19,20,21,23,24).…”
Section: Discussionunclassified